Perception of products of landscape painting us the factor of formation of art-aesthetic experience of students (Pedagogy of Higher and Secondary Education, 2006)
Article is devoted to a problem of formation of the creative person of the future teacher of disciplines of art. Approaches to formation of art-aesthetic experience of students are proved by perception ofproducts of landscape pointing, and also mechanisms of this process are opened
Keywords: art-aesthetic experience; perception of works of art; reflection; art-creative self-realization